Kiai Kampung and Traditional Islamic Orthodoxy: A Socio-religious Study of Mosque-based Authority in Rembang, Central Java, Indonesia - Ja'far, Ali (LP2M - Universitas Islam Negeri Walisongo Semarang, 2024)
The role of kiai kampung as local religious authorities in Indonesia has evolved dynamically in response to shifting socio-political landscapes and changing patterns of Islamic religious authority. This paper examines the role of kiai kampung as socio-religious agents in managing mosques and preserving traditional Islamic orthodoxy in Indonesia's Reform era. Kiai kampung effectively translates Islamic principles to grassroots levels as they influence social, religious, and political discussions through regular preaching and sermons (khutbah). The study uses field research to observe da'wah practices and institutional affiliations in Rembang, Central Java. Using the concepts of agency and cultural broker, this study finds that kiai kampung does not merely reproduce inherited traditions but actively reinterprets them in response to contemporary socio-political challenges. This study contributes to the idea that, besides kiai kampung promoting a distinct model of traditional orthodoxy, their affiliation with religious institutions enables them to shape local religious and political discourse while supporting government agendas aligned with Islamic values. This support is often expressed through sermons referencing classical religious texts, including tafsir, hadith, and tasawuf (Sufism). As grassroots leaders, kiai kampung also contributes to the institutional growth of santri communities in Indonesia's Reform era.